Antistress Effects of the Ethanolic Extract from Cymbopogon schoenanthus Growing Wild in Tunisia. (8th October 2013) - Ben Othman, Mahmoud; Han, Junkyu; El Omri, Abdelfatteh; Ksouri, Riadh; Neffati, Mohamed; Isoda, Hiroko
Abstract : This study aimed to investigate the antistress properties of the ethanol extract of Cymbopogon schoenanthus (CSEE), growing wild in the southern part of Tunisia. The effect of extracts on H2 O2 -induced cytotoxicity and stress in human neuroblastoma SH-SY5Y cells. Its effect on stress-induced in ICR mice was exposed to force swim and tail suspension, in concordance with heat shock protein expression (HSP27 and HSP90), corticosterone, and catecholamine neurotransmitters level. Our results demonstrated that pretreatment of SH-SY5Y cells with CSEE at 1/2000, 1/1000, and 1/500 v/v dilutions significantly inversed H2 O2 -induced neurotoxicity. Moreover, CSEE treatments significantly reversed heat shock protein expression in heat-stressed HSP47-transformed cells (42°C, for 90 min) and mRNA expression of HSP27 and HSP90 in H2 O2 -treated SH-SY5Y. Daily oral administration of 100 mg/kg and 200 mg/kg CSEE was conducted to ICR mice for 2 weeks. It was resulted in a significant decrease of immobility time in forced swimming and tail suspension tests. The effect of CSEE on animal behavior was concordant with a significant regulation of blood serum corticosterone and cerebral cortex levels of catecholamine (dopamine, adrenaline, and noradrenaline). Therefore, this study was attempted to demonstrate the preventive potential of CSEE against stress disorders at in vitro and in vivo levels.